Nonconforming gender expression and insufficient sleep among adolescents during COVID-19 school closure and after school reopening - Qiguo Lian; Chaohua Lou; Xiangyang Zhong; Jiashuai Zhang; Xiaowen Tu; Yuhang Fang; Chunyan Yu; Xiayun Zuo (BMC, 2022)
Abstract Background Gender nonconformity (GNC) (i.e., gender expression that differs from gender role expectations for feminine or masculine appearance and behavior) is an under-researched area of adolescent sleep health. The COVID-19 lockdown offers an opportunity to understand how the effect of GNC on adolescent health outcomes changes between school closure and reopening. Methods We conducted a cross-sectional study in Shanghai, China, in 2020. The sample size for analysis was 3,265. The age-specific insufficient sleep was estimated according to National Sleep Foundation's sleep duration recommendations. The self-perceived and self-rated GNC were measured by the two items "On the same scale that goes from 100% as a girl to 100% as a boy, where do you think others see you?" and "On a scale that goes from feeling 100% like a girl to feeling 100% like a boy, where do you see yourself?", and birth sex. In addition, we calculated sex-stratified adjusted odds ratios (AORs) of insufficient sleep for students with high and moderate GNC compared to students with low GNC. Finally, we measured the AORs with self-perceived and self-rated GNC during COVID-19 school closure and reopening. Results Among 3,265 students in grade 6-12 in the analytic sample, 1,567(48.0%) were assigned female at birth (AFAB), 3,188 (97.6%) Han, and 1,921(58.8%) in grade 6-9. Among AFAB students, high self-perceived GNC was significantly associated with insufficient sleep (AOR,1.65; 95%CI,1.30-2.09) during school closure. Insufficient sleep was associated with high self-rated GNC (AOR,1.73; 95%CI,1.23-2.44) and moderate self-rated GNC (AOR,1.69; 95%CI,1.29-2.22) during school closure. After school reopening, neither self-perceived nor self-rated GNC was associated with insufficient sleep among AFAB students. Among assigned male at birth (AMAB) students, none of the two kinds of GNC was associated with insufficient sleep in the two periods during the COVID-19 pandemic. Conclusions This study suggests GNC is only associated with insufficient sleep among AFAB students during school closure. Furthermore, the association is nonsignificant among AMAB students. These findings indicate that GNC-related stigma within the family could be a risk factor for insufficient sleep among AFAB adolescents.